Evaluation of Free Radical Scavenging and Polyphenolic Contents of Bark of Pterygota alata Roxb (Journal of Scientific Research, 2014)
Pterygota alata is a large deciduous tree of Malvaceae family. The present study was designed to evaluate in vitro antioxidant activity of stem bark of the plant. Ferric reducing power (FRP) test, 1, 1- diphenyl-2-picryl hydrazyl (DPPH) free radical scavenging test and total antioxidant capacity (TAC) assay were used to detect the antioxidant activity. Total phenolic and flavonoid contents were also determined as they are well known phytochemicals with antioxidant property. The bark of the plant showed efficient reducing power as well as free radical scavenging property (IC50 values 52.25 - 172.05). The bark also found rich in total phenolic and flavonoid content. The highest amount of total phenolic content was found in chloroform soluble fraction (29.898 µg/mL) followed by ethyl acetate soluble fraction (15.88 µg/mL). The highest content of total flavonoid also detected in chloroform soluble fraction (107.56 µg/mL) but followed by crude ethanol extract (98.66 µg/mL). Overall, the bark of the plant possesses significant antioxidant activity, therefore can be used as a good natural source of antioxidant. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.17586 J. Sci. Res. 6 (3), 543-552 (2014)